1992
DOI: 10.1111/j.1472-8206.1992.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and pharmacokinetics of propacetamol, a paracetamol formulation for intravenous use

Abstract: In 12 healthy volunteers, paracetamol pharmacokinetics were compared following administration of 1 g propacetamol HCl given intravenously over a 15-min period and 500 mg paracetamol given orally. Mean +/- SD total AUC (microgram/ml.h) following the iv formulation was significantly (P < 0.01) greater than following oral paracetamol (25.53 +/- 4.27 vs 21.04 +/- 4.49) corresponding to a mean oral bioavailability of paracetamol of 82.2 +/- 9.4%. Between 1 and 2 h after administration, paracetamol plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 6 publications
4
48
0
Order By: Relevance
“…Prodrug of paracetamol that can be administered parenterally when greater efficacy or a fast onset of analgesia is desirable. IV infusion of propacetamol 2 g was significantly more effective than paracetamol 1 g taken orally in patients with moderate to severe postoperative pain after hallux valgus surgery (13,14). There are conflicting results concerning preemptive and preventive administration of different groups of analgesics.…”
Section: Discussionmentioning
confidence: 91%
“…Prodrug of paracetamol that can be administered parenterally when greater efficacy or a fast onset of analgesia is desirable. IV infusion of propacetamol 2 g was significantly more effective than paracetamol 1 g taken orally in patients with moderate to severe postoperative pain after hallux valgus surgery (13,14). There are conflicting results concerning preemptive and preventive administration of different groups of analgesics.…”
Section: Discussionmentioning
confidence: 91%
“…At these times, the reduction obtained for the pH values of the solutions was of approximately 1 pH unit, which is worth considering because the pH of the solution is important in local intolerance to parenteral administration. Despite the low pH of the solutions, Depré et al 8) reported that the local and systemic tolerability of 1 g and 2 g of PRO given intravenously was excellent.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] In these circumstances, PRO can be administered in physiologic or glucose solutions since it is rapidly and quantitatively hydrolyzed into PA by plasma estearases within 7 min after intravenous injection. 8) With the exception of absorption, PRO exhibits similar disposition kinetics when given by either the intravenous route as PA or by mouth as conventional tablets. 14) Screening of the literature revealed that PRO can be analytically determined by first-derivative spectrophotometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological effects in clinical trials have shown that 2 possesses efficacy similar to that of 1. However, due to its greater water solubility, it can be parenterally administered and thus be employed when oral administration is not possible (5). Phthalimide derivatives have been widely reported to possess beneficial pharmaceutical effects, like analgesic (7), antiinflammatory (8) and antiviral (9) activities.…”
Section: Introductionmentioning
confidence: 99%